A Study on Youth Perception towards Digital Wallets in Post COVID-19 Pandemic in Kathmandu Valley - Aryal, Prashant (Nepalese Journal of Management, 2025)
This study examines the youth perception towards digital wallets in post COVID-19 Pandemic that are located inside Kathmandu valley. Youth perception of digital wallet is selected as the dependent variable. Similarly, intention to use, perceived usefulness, perceived ease of use, trustworthiness, IT skills and Internet access are selected as independent variables. The study is based on primary data with 125 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing impact on youth perception of digital wallet in post COVID-19 Pandemic in Kathmandu valley. The study showed that intention to use has a positive impact on youth perception of digital wallet. It means that an increase in intention to use leads to an increase in youth perception of digital wallets. Similarly, the perceived usefulness has a positive impact on youth perception of digital wallets. It indicates that an increase in perceived usefulness leads to an increase in youth perception of digital wallets. Likewise, perceived ease of use has a positive impact on youth perception of digital wallets. It means that an increase in perceived ease leads to an increase in youth perception of digital wallets. Similarly, trustworthiness has a positive impact on youth perception of digital wallets. It shows that an increase in trustworthiness leads to an increase in youth perception of digital wallets. Likewise, IT skills has a positive impact on youth perception of digital wallets. It shows that better in IT skills leads to better in youth perception of digital wallets. Similarly, the Internet access has a positive impact on youth perception of digital wallets. It shows that the increase in internet access leads to an increase in effective youth perception of digital wallets.